Effects of previous ovarian drilling on cumulative ongoing pregnancy rates among patients with polycystic ovarian syndrome undergoing in vitro fertilization. Issue 3 (September 2016) - Cai, Jiali; Liu, Lanlan; Sun, Lingbin; Sha, Aiguo; Jiang, Xiaoming; Ren, Jianzhi
Abstract: Objective: To determine if history of undergoing laparoscopic ovarian drilling (LOD) was associated with changes in cumulative ongoing pregnancy rates following in-vitro fertilization in patients with polycystic ovary syndrome (PCOS). Methods: The present retrospective study was performed in an in vitro fertilization unit in Xiamen, China, between June 1, 2008 and December 31, 2012. Patient characteristics and in vitro fertilization treatment outcomes were compared between patients with PCOS and a history of LOD (LOD group), patients with PCOS without a history of LOD (no-LOD group), and age-matched patients without PCOS and with no history of LOD (age-matched group). Results: The study included 110 patients in the LOD group, 127 patients in the no-LOD group, and 990 patients in the age-matched group. A lower number of retrieved oocytes, fewer available embryos, and a lower number of cryopreserved embryos were observed in among patients in the LOD-group compared with the other groups ( P ≤ 0.001). No differences in birth rates following fresh embryo transfers were observed between the LOD-group, and the age-matched group ( P = 0.274) and the no-LOD group ( P = 0.120). A higher adjusted odds ratio of cumulative pregnancy per initiated in vitro fertilization cycle was observed in the no-LOD group when compared with the LOD group (1.976; 95% confidence interval 1.091–3.580). Conclusion: LOD could compromise cumulative ongoing pregnancy rates during subsequent in vitro fertilization.